Equity: now assisting volunteers? A case comment on Khan v Mahmood [2021] EWHC 597 (Ch). Issue 2 (18th December 2021) - Freeman, Matthew; Pullar, Zachariah
Abstract: The decision in Khan v Mahmood is a further example in recent years of the High Court grappling with the issue of when a gift, imperfect at law, might yet be complete in equity. The case is notable for how it treated (or omitted to treat) key authorities on imperfect gifts; its approach to, and analysis of the Pennington v Waine 'unconscionability' test; and the broader implications of the direction of travel established by Pennington for equity's conventional stance that it 'will not assist a volunteer'.